Passing the Word: Toward a Model of Gossip and Power in the Workplace - Kurland, Nancy B.; Pelled, Lisa Hope (Academy of Management Review, 2000)
Although gossip is widespread, seldom has it been a topic of management research. Here the researchers build a conceptual model of workplace gossip and its effects on the power of employees who initiate it. After defining and distinguishing among different kinds of workplace gossip, the researchers develop propositions about the effect of that gossip on gossipers' expert, referent, reward, and coercive power. They then suggest how moderators may shape those effects and discuss implications of the model.